Mid-infrared spectroscopic instrumentation for airborne monitoring of atmospheric gas species - Davis, Nicholas Mark (Cranfield University, 2018)
Methane is a colourless, odourless gas that can be found extensively in nature. The average global concentration of methane is currently approximately 1.8ppm, the highest concentration for over 800,000 years. Although this concentration is signi cantly lower than that of CO₂ (391ppm), methane has a global warming potential up to 34 times greater over a hundred year period. As a result, trace detection of atmospheric methane has gained increased attention as a form of environmental protection. The purpose of this thesis is to undertake investigations into the development of instrumentation to make observations of background levels of atmospheric methane. Newly available wavelength sources along with alternative gas cells are investigated for potential use in this instrument. Laboratory analysis of a new external cavity Bragg-stabilised laser (ECBSL) operating at 1651nm was performed, with comparisons made against against a bre-coupled distributed feedback (DFB) laser diode. The ECBSL showed promise for use in the detection of methane in the laboratory, with a limit of detection of 8ppm using a 25cm pathlength single-pass gas cell being comparable to that of the DFB laser diode. Issues with alignment stability were however observed with this laser, limiting the measurements that could be made and restricting its use outside of laboratory conditions, with utilisation on light aircraft deemed to be impossible in its current con guration. Investigations were then performed into the performance of a newly available interband cascade laser (ICL), with emission at 3311nm. A full characterisation of the ICL was performed, alongside measurements of methane using both a 25cm pathlength single-pass cell and an integrating sphere with e ective pathlength of 54.5cm, with single-point limits of detection of 2.2ppm and 1.0ppm being determined respectively. A combination of an Allan variance and absorption line- tting techniques were utilised to improve the limit of detection using the integrating sphere, resulting in a 0.3ppm limit of detection for a 25 second average. The design and development of instrumentation to perform measurements of background concentrations of atmospheric methane utilising the combination of ICL and integrating sphere is then described. The reasoning behind the selection of components and progression of the instrument design is described. Once assembled, laboratory testing of the instrument showed a single-point limit of detection of 1.6ppm, higher than that seen with the previous set-up, however this was still below the background methane concentration. An initial shakedow flight was carried out once the instrument had been certi ed and installed in the aircraft. Due to failures of two electrical components, further flight testing was postponed until improvements to component isolation have been made. This flight demonstrated, however, that the instrument has the potential to provide measurements of atmospheric methane, as the majority of components operated as expected, including both the laser and the cell optics.